Consumers’ Perceptions, Attitudes and Willingness to Pay Towards Chemical Free Vegetable in North Sumatera - Khair, Hadriman (2004)
This study was aimed to determine consumers’perceptions, attitudes and willingness to pay (WTP) towards chemical free vegetable (CFV) produce in North Sumatra Province.A total of 2080 respondents were interviewed using a close-ended questionnaire.Collected data was analysed using descriptive analysis, factor analysis and contingent valuation method (CVM).The results indicated that more than half of the respondents have consumed CFV.The result showed that lack of knowledge of CFV and the place to purchase CFV were the main reasons for consumers not consuming CFV.Nutritional value was an important factor that influences consumers’preferences in purchasing CFV, followed by desire, freshness, health effect and taste.The factor analysis identified nine factors that influenced the purchase of CFV among North Sumatra Province consumers.The factors were government involvement,health consciousness,consumer influence to purchase,product availability,awareness of chemical use, product appearance,information awareness, market potential and consumer awareness to consume.Contingent Valuation Method was used to estimate consumers’ WTP for CFV.A logit and probit model was used to determine consumers’WTP a premium for CFV.The results indicate that gender, household income, price level,marital status and household member below 17 years old were the most important and significant factors that influenced and determined the amount of premium that a consumer is willing to pay for CFV.Based on the study,it was found that at present, CFV market is still a niche market,catering only to a small segment of the whole vegetable market in North Sumatra Province. Generally, North Sumatra Province consumers’ have the potential to purchase CFV produce. Thus, there is a need for the proper development of an effective CFV market and the establishment of standards and certification program for CFV